A model of chronic enthesitis and new bone formation characterized by multimodal imaging - Christine Czegley; Clarissa Gillmann; Christine Schauer; Lisa Seyler; Christiane Reinwald; Madelaine Hahn; Michael Uder; Katja Jochmann; Elisabeth Naschberger; Michael Stock; Georg Schett; Tobias Bäuerle; et al. (The Company of Biologists, 2018)
Enthesitis is a key feature of several different rheumatic diseases. Its pathophysiology is only partially known due to the lack of access to human tissue and the shortage of reliable animal models for enthesitis. Here, we aimed to develop a model that mimics the effector phase of enthesitis and reliably leads to inflammation and new bone formation. Enthesitis was induced by local injection of monosodium urate (MSU) crystals into the metatarsal entheses of wild-type (WT) or oxidative-burst-deficient (Ncf1**) mice. Quantitative variables of inflammation (edema, swelling) and vascularization (tissue perfusion) were assessed by magnetic resonance imaging (MRI), bone-forming activity by [18F]-fluoride positron emission tomography (PET), and destruction of cortical bone and new bone formation by computed tomography (CT). Non-invasive imaging was validated by histochemical and histomorphometric analysis. While injection of MSU crystals into WT mice triggered transient mild enthesitis with no new bone formation, Ncf1** mice developed chronic enthesitis accompanied by massive enthesiophytes. In MRI, inflammation and blood flow in the entheses were chronically increased, while PET/CT showed osteoproliferation with enthesiophyte formation. Histochemical analyses showed chronic inflammation, increased vascularization, osteoclast differentiation and bone deposition in the affected entheseal sites. Herein we describe a fast and reliable effector model of chronic enthesitis, which is characterized by a combination of inflammation, vascularization and new bone formation. This model will help to disentangle the molecular pathways involved in the effector phase of enthesitis.